Perbaikan Kualitas Dadih Susu Kerbau Murrah Menggunakan Bahan Kemasan - Sigit Sepriadi (Universitas Sumatera Utara, 2012)
ABSTRACT Curd is kind of the probiotic fermentation food contained high level of nutrition. It is easy to be digested and be absorbed by body. This study investigated the effect of packaging which were without packaging, flexibel packaging and cup packaging as packaging stuff of curd on its organoleptic properties and its acceptability. This research is conducted in Silangit Village, Siborong-borong Sub District Tapanuli Utara District started in December 2011 until April 2012. The research was used a compeletely random design with one factor that is fermentation time (7 days). The organoleptic properties and acceptability of curd were measured by Friedman test. LSD (Least Significant Difference) test was used to compare the significant difference. The research showed that the using of different packaging stuff of curd were affecting its organoleptic properties, such as color, aroma, taste, and compactness. However, there was a difference ini their texture properties. The sing of flexibel packaging showed the highest level of panelist acceptance, value of benefit cost ratio showed 1.82. Keyword :Curd, Buffalo Milk, Packaging, Organoleptic